"Food is more than just a source of nutrients": A qualitative phenomenological study on Food Involvement. (1st November 2022) - Castellini, Greta; Graffigna, Guendalina
Abstract: The role of food in people's life has changed dramatically in recent years. In particular, it is becoming more symbolic and linked to subjective values. For this reason, recent scientific research has delved into the construct of Food Involvement. However, to the best of our knowledge, there are no empirical studies aimed at exploring this construct deepening the symbolic value assumed by it. Accordingly, the current study aims to qualitatively explore the personal meanings that consumers attribute to Food Involvement and to detect the psychological domains that characterize this lived experience. The study included a purposive sample of adults selected according to three different prototypical profiles until reaching data saturation: mothers, cooks or athletes, all with medium or high levels of Food Involvement. Fourteen in-depth phenomenological interviews were conducted and analyzed according to the principles of Interpretative Phenomenological Analysis (IPA). Results showed that Food Involvement is characterized by a deep relationship between the consumer and food that allows satisfying one's ambitious transformative project that involves the self, the other or both actors. This symbolic role played by Food Involvement was recognized by both those with medium or high involvement. However, the orientations in one's transformative process of mothers, athletes and cooks is different. In particular, the transformative project of mothers is oriented towards the other, that of cooks towards the self and athletes' project towards the self and others. This study gives a scientific contribution to the literature about Food Involvement to create effective measurement scales that assess the symbolic role that Food Involvement has in people's lives.